2017
DOI: 10.1002/adsc.201600933
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Silver Dual Catalyzed Decyanative C–Se Cross‐Coupling

Abstract: Traditionally, a metal‐catalyzed cross‐coupling reaction is governed by displacement of leaving groups such as halogens, tosylates, etc. by different nucleophiles leading to the formation of carbon‐carbon and carbon‐heteroatom bonds. Besides displacement of traditional leaving groups in coupling reactions decyanative cross‐coupling has also received current attention. The objective of this work is to develop a decyanative cross‐coupling through metal‐assisted nucleophilic displacement, which is less explored s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…At the same time, similar to thiocyanate derivatives, selenocyanate derivatives also play a good role in many fields for their significant bioactivity and good reactivity . However, compared with the synthesis of vinyl thiocyanate derivatives, the construction of vinyl selenocyanate derivatives is rare,[11d] even recently a three‐component reaction method based on activated alkyne has recently been successfully developed .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, similar to thiocyanate derivatives, selenocyanate derivatives also play a good role in many fields for their significant bioactivity and good reactivity . However, compared with the synthesis of vinyl thiocyanate derivatives, the construction of vinyl selenocyanate derivatives is rare,[11d] even recently a three‐component reaction method based on activated alkyne has recently been successfully developed .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all describe the functionalisation of the 3‐position, furnishing 3‐selenylindoles. To the best of our knowledge, there is only one protocol where the authors identified a 2‐substituted selenylindole as a by‐product in a coupling reaction between arylselenocyanate and 2‐ethynylaniline catalysed by Cu(OAc) 2 and Ag 2 CO 3 , in an attempt to synthesise chalcogenoalkynes …”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge,t here is only one protocol where the authors identified a2 -substituted selenylindole as ab y-product in ac oupling reactionb etween arylselenocyanate and 2-ethynylaniline catalysed by Cu(OAc) 2 and Ag 2 CO 3 ,i na na ttempt to synthesise chalcogenoalkynes. [8] Given the reactivity of the indole ring, and the well-established conditions in functionalisation reactions for the synthesis of 3-selenylindoles, there is clearly al ack of development of new strategies for functionalisation in position 2. With this criterion in mind, and in consonance with our continuing interest in the synthesis of organoselenium compounds, [9] we designed as elenium-containing precursor,c onsidering as ubsequent cyclisation step for indole construction in which the functionalised position was pre-defined.…”
Section: Introductionmentioning
confidence: 99%
“…Except selenium-based reagents, other coupling partner like organosilanes also have been explored for the said conversion. [27][28] Organosilanes are well known for their applications in Hiyama coupling as they are inexpensive compared to other coupling partners. Apart from it, organosilanes posed a problem of their low reactivity which can be tackled by the use of fluoride source.…”
Section: Introductionmentioning
confidence: 99%